Supported Palladium Nanoparticles‐Catalyzed Synthesis of 3‐Substituted 2‐Quinolones from 2‐Iodoanilines and Alkynes Using Oxalic Acid as C1 Source. Issue 3 (5th December 2018) - Thakur, Vandna; Sharma, Ajay; Yamini,; Sharma, Nishtha; Das, Pralay
Abstract: 3‐Aryl/alkyl‐2‐quinolones were synthesized employing microwave assisted multicomponent reaction of 2‐iodoanilines, terminal alkynes and oxalic acid dihydrate ((CO2 H)2  ⋅ 2H2 O) under polystyrene supported palladium (Pd@PS) nanoparticles‐catalyzed conditions. The use of a heterogeneous palladium catalyst was explored first time for 2‐quinolone synthesis involving carbonylation reaction employing (CO2 H)2  ⋅ 2H2 O as a solid and bench stable carbon monoxide (CO) source. The reaction exhibited good substrate generality for 2‐iodoanilines and alkynes with wide functional group tolerance and good regio‐selectivity. The ligand free operation, recyclability of heterogeneous Pd@PS catalyst and use of bench stable C1 source are the invaluable merits of the protocol. Abstract :